2011
DOI: 10.1249/mss.0b013e318216ea50
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity as a Long-Term Predictor of Peak Oxygen Uptake

Abstract: Physical activity level at baseline was positively associated with directly measured cardiorespiratory fitness (VO(2peak)) 23 yr later. People who changed from low to high activity during the observation period had substantially higher V˙O(2peak) at follow-up compared with people whose activity remained low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
4
29
0
1
Order By: Relevance
“…This may have attenuated the parent-offspring associations in the physical activity analyses. However, validation studies have shown that questionnaires may be useful for classifying people into broad categorisations of physical activity,33 and a recent study showed that the questions used in this study were a good long-term predictor of cardiorespiratory fitness 34…”
Section: Discussionmentioning
confidence: 77%
“…This may have attenuated the parent-offspring associations in the physical activity analyses. However, validation studies have shown that questionnaires may be useful for classifying people into broad categorisations of physical activity,33 and a recent study showed that the questions used in this study were a good long-term predictor of cardiorespiratory fitness 34…”
Section: Discussionmentioning
confidence: 77%
“…Most research examining the relationship between PA and CRF, has used PA as an independent variable and CRF as a dependent variable. In this tradition, Aspenes et al (Aspenes, Nauman, Nilsen, Vatten, & Wisloff, 2011) found that self-reported PA level at baseline was positively associated with CRF 23 years later, while Loe et al (Loe, Rognmo, Saltin, & Wisloff, 2013) found a poor overall correlation (r=0.24) between self-reported PA level and oxygen uptake. In contrast to these studies we used CRF as an independent variable in our statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the strongest single correlate of overall PA, CRF, was measured by direct ergospirometry instead of using estimated CRF values or substitute measures of CRF, which is more common in large population-based public health studies (Aspenes et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have suggested that non-exercise models can be valid predictors of VO 2 peak for heterogeneous samples [11] and can give relatively accurate results conveniently [5]. Recently, Aspenes et al (2011) [3] have further suggested that "valid and reliable physical activity questionnaires that predict cardiorespiratory fitness may be valuable instruments for monitoring physical fitness in a population, when more costly and time-consuming techniques are not feasible".…”
Section: Discussionmentioning
confidence: 99%